Electrosynthesis of binuclear ruthenium complexes from [RuCl3(dppb)(L)] precursors [L = pyridine, 4-methylpyridine or dimethyl sulfoxide; dppb=1,4-bis(diphenylphosphino)butane] - Wohnrath, K.; de Araujo, M. P.; Dinelli, L. R.; Batista, A. A.; Moreira, I. D.; Castellano, E. E.; Ellena, J. (Royal Soc Chemistry, 2000)
Electrolysis has been examined as a method of synthesis for [(L)(dppb)Ru(mu-Cl)(3)RuCl(dppb)] complexes, where dppb = 1,4-bis(diphenylphosphino)butane and L = pyridine (py), 4-methylpyridine (4-pic) or dimethyl sulfoxide (DMSO), by using [RuCl3(dppb)(L)] as precursors. The products of the electrolysis were characterized by P-31-{H-1} NMR, cyclic voltammetry and near infrared spectroscopy. The presence of the [Ru2Cl5(dppb)(2)] complex in the electrochemical cell suggests a mechanism by which the starting original species from the bulk solution reacts with the reduced form [RuCl2(dppb)(L)] generated at the surface of the electrode. The crystal structure of the precursor mer-[RuCl3(dppb)(4-pic)] was determined by X-ray diffraction.